Preoperative Transarterial Embolization of Malignant Tumors of the Extremities (Current State of the Problem) (Review) - Solonitsyn, Ye.O.; Protsenko, V.V. (TERRA ORTHOPAEDICA, 2020)
Summary. The article considers current issues of modern medicine, in particular the use of the method of transarterial embolization of blood vessels in the treatment of malignant tumors of the extremities. The purpose, indications, technical features and materials used for its implementation, as well as contraindications and complications are highlighted. Its efficiency in preparation of the patient for a surgery of musculoskeletal malignant tumor is considered. Analysis of the modern domestic and foreign literature shows that now indications for use of this method expand, and technical possibilities of the equipment and physical and chemical properties of materials improve. The issues of further study and development of the problem are outlined.